Digital expansionism and big tech companies: consequences in democracies of the European Union - Carlos Saura García (Humanities & Social Sciences Communications, 2024)
Abstract Big digital companies have become key elements in economy, communication, education, and politics in 21st century societies. The neutral ideology in their digital platforms, applications, and services, as well as the exponential growth in their activities can be used by world superpowers —especially the United States and China— to implement geostrategical operations, massive social manipulation or influence democratic processes with the objective of increasing their power and dominance over other nations. The aim of this paper is to state the different strategies of digital expansionism performed by the United States and China, and, additionally, to showcase the negative consequences of these strategies on the population and democracies of the European Union. The first section of this paper will define the concepts of digital sovereignty and digital expansionism as well as their importance in 21st century geopolitics. Next, the important role that big digital companies have on digital expansionism will be analysed, and the usage of digital authoritarianism and digital instrumentarianism performed by the United States and China will be further examined. Finally, the negative consequences of the implementation of these methods in the democratic systems of the European Union will be analysed, as well as what possible solutions there might be for said consequences.